Architecture and Body Associates in Newari Culture of Bhaktapur - Dhungana, Kishor; Kawan, Shyam Sunder (Journal of Advanced Research in English & Education, 2023)
This study investigates Newari culture of Bhaktapur, which strongly links architecture to the human body. The design and construction of traditional Newari buildings, which are sometimes referred to as "living structures" meant to resemble human bodies, reflect this. The traditional Newari homes  which are constructed around a central courtyard and frequently have multiple stories, are one illustration of this relationship follow the structure of "Vaastu Purusha"  . The layout of the house is intended to resemble the human body, with the central courtyard representing the heart and the various rooms and floors representing different parts of the body. The woodcarvings that adorn many Newari buildings are often based on the human form, with intricate carvings of faces, hands, and feet. These carvings are intended to bring life and vitality to the building, much like the human body. In addition, many Newari festivals and celebrations involve the construction of temporary structures, such as "Mandala" or "Tudal," that are also designed to resemble the human body. For example, during the Gai Jatra festival, held in honor of those who have passed away in the previous year, a procession is held in which participants dress up in costumes that represent various parts of the body, such as eyes, ears, and hands.